DISTRIBUTION OF LEACHATE POLUTION IN THE FINAL DISPOSAL OF PIYUNGAN, BANTUL, YOGYAKARTA, BY USING THE ELECTROMAGNETIC METHOD - , Sismanto , Eddy Hartantyo ([Yogyakarta] : HAGI-IAGI-PERHAPI, 2005)
Besides, the Piyungan final waste disposal with 20 ha squares has an important function of urban waste disposal from Kodya, Bantul, and Sleman districts